Three Horizons for Future Geoscience - Iain Stewart; Maria Angela Capello; Hassina Mouri; Kombada Mhopjeni; Munira Raji (Earth Science, Systems and Society)
Geoscience, along with other scientific disciplines, is being increasingly challenged on how it can best confront key global challenges, such as climate change, food insecurity, biodiversity loss, human conflict and migration, and persistent poverty. But its traditional association with exploitation of the planet’s natural resources for energy and materials links it with contemporary concerns around unsustainable human practices, arguably fueling a growing disenchantment that is most evident in declining enrollment in university geoscience courses in many countries. Therefore, a fresh re-framing of the geoscience’s relationship to society would seem to be urgently needed. In response to this need, we introduce the “Three Horizons” concept for visualizing paradigm change in complex systems as a tool to explore how the future global geoscientific mission might be re-imagined. Using this conceptual framework, we consider three parallel pathways – “business as usual” (horizon 1), “entrepreneurial” (horizon 2) and “visionary” (horizon 3)—that offer alternative narrative trajectories for how geoscience and geoscientists might serve society’s grand challenges.